2006
DOI: 10.2741/1786
|View full text |Cite
|
Sign up to set email alerts
|

Phytate (Myo-inositol hexakisphosphate) inhibits cardiovascular calcifications in rats

Abstract: Calcification is an undesirable disorder, which frequently occurs in the heart vessels. In general, the formation of calcific vascular lesions involves complex physicochemical and molecular events. Calcification (hydroxyapatite) is initiated by injury and is progressed by promoter factors and/or the deficit of inhibitory signals. Myo-inositol hexakisphosphate (phytate, InsP6) is found in organs, tissues and fluids of all mammals and exhibits an important capacity as a crystallization inhibitor of calcium salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…A previous study using both vitamin D (300,000 IU/kg im) and nicotine (25 mg/kg po) reported higher levels of calcification in the rats' arteries and hearts compared with the current study. 32 That study used lower levels of vitamin D, and thus involved lower levels of calcium phosphate supersaturation than the present study. These observations demonstrate the importance of a preexisting lesion (caused by nicotine in the other study) in the development of tissue calcification.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…A previous study using both vitamin D (300,000 IU/kg im) and nicotine (25 mg/kg po) reported higher levels of calcification in the rats' arteries and hearts compared with the current study. 32 That study used lower levels of vitamin D, and thus involved lower levels of calcium phosphate supersaturation than the present study. These observations demonstrate the importance of a preexisting lesion (caused by nicotine in the other study) in the development of tissue calcification.…”
Section: Discussionmentioning
confidence: 61%
“…A previous study found that phytate could inhibit vitamin D and nicotine-induced calcification in both the aorta and the heart of Wistar rats. 32 The difference between the findings of the 2 studies may be related to less lesions in the absence of nicotine, and that as a consequence of the higher hydroxyapatite supersaturation (because of increased blood calcium and phosphorus levels), the calcium deposits may have developed directly through homogeneous nucleation and not as a consequence of hydroxyapatite heterogeneous nucleation induced by the injured tissue. The tissue calcium content data for the 2 studies shows that more calcium was deposited when using vitamin D and nicotine than using only high vitamin D doses, despite the former experiments being half the duration of the latter.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…They also affect the quality and quantity of calcium phosphate crystals. Zinc salts have been reported to reduce plaque acidogenicity and growth (Grases et al, 2006). Toothpastes containing zinc salts, such as zinc citrate and zinc chloride, have been shown to be effective in deceasing calculus formation.…”
Section: Strategies For Prevention Of Calculus Formationmentioning
confidence: 98%
“…Proanthocyanidin-treated pericardial tissues are non-cytotoxic and resist against enzyme digestion, and have been shown to be compatible with cell attachment and proliferation. Phytate has been suggested as an anticalcification reagent (Grases et al, 2006(Grases et al, , 2008 and has achieved promising results, to be validated by further studies. Other amide-type crosslinks, based on the activation of carboxyl groups, have been studied, such as diphenylphosphorylazide or ethyldimethylaminopropyl carbodiimide.…”
Section: Cross-linking Treatment Of Pericardial Tissuementioning
confidence: 99%